Child Growth During the First 1000 Days of Life in Lebanon: Sex of the Child Matters. (29th May 2020) - Chehab, Rana; Forman, Michele; Nasreddine, Lara
Abstract: Objectives: The study examines the relation between sociodemographic, maternal, and child characteristics and sex-specific anthropometric status of children using a hierarchical conceptual framework. Methods: A cross-sectional study of a nationally representative sample of mothers and children aged ≤5 years was conducted in Lebanon. This analysis focuses on children aged 4 months-2 years ( n =406) stratified by child's sex. Multiple linear regression models were fitted for length-for-age (LAZ), weight-for-age (WAZ), and weight-for-length z-scores (WLZ) applying a hierarchical conceptual framework with variables at distal, intermediate and proximal levels. Results: Overall, means ± SD for LAZ, WAZ and WLZ were: −0.24 ± 1.4, 0.46 ± 1.1 and 0.75 ± 1.2 among boys and −0.08 ± 1.2, 0.41 ± 0.96 and 0.63 ± 1.0 among girls, respectively. At the distal level, maternal and paternal attainment of university degrees were respectively associated with higher LAZ (B: 0.81, 95% CI: 0.1, 1.5) and lower WLZ (B: −0.62, 95% CI: −1.2, −0.09) among boys. On the other hand, higher crowding index was associated with lower LAZ (B: −0.64, 95% CI: −1.14, −0.13) while maternal employment was associated with higher WAZ (B: 0.37, 95% CI: 0.06, 0.67) among girls. At the intermediate level, higher maternal BMI was associated with lower LAZ (B: −0.03, 95% CI: −0.06, −0.00) and higher WLZ (B: 0.03, 95% CI: 0.00, 0.06) among girls. Taller mothers were more likely to have boys and girls with higher LAZ (B: 0.06, 95% CI: 0.03, 0.09 for both) and girls with higher WAZ (B: 0.02, 95% CI: 0.00, 0.05). Among the proximal factors, longer boys and girls at birth had higher WAZ (B: 0.06, 95% CI: 0.004, 0.12 and B: 0.05, 95% CI: 0.005, 0.092, respectively). Breastfeeding for 4 months or more was associated with lower WAZ (B: −0.54, 95% CI: −0.83, −0.24) and WLZ (B: −0.33, 95% CI: −0.62, −0.03) among girls. Conclusions: Differentdistal, intermediate, and proximal factors were associated with sex-specific anthropometric indicators in Lebanon. Future research should account for sex differences using similar frameworks to inform interventions to improve child growth. Funding Sources: This research was funded by the Lebanese National Council for Scientific Research and the American University of Beirut Research Board.